Internationalization of higher education: mainland Chinese students’ first year experience in Hong Kong - Ma, Yuk Yi Anna (2021)
International mobility in higher education (HE) has been exponentially expanding and on a consistent basis over the past decade. Hong Kong is a society which is both familiar and strange to Mainland Chinese students because of the unique and different political and sociocultural relationships in comparison to their homeland. The Chinese University of Hong Kong (CUHK) is the only bilingual higher education institution in Hong Kong and this makes it attractive to Mainland Chinese students. While previous research have examined the phenomenon of international students choosing to enroll in English-medium universities in top destinations like the United States, the United Kingdom, Australia, France and Germany, little research has been done in Hong Kong, where English medium is a highly contested issue. To fill the research gap, this thesis examines mainland Chinese students’ adaptation experiences upon arrival in Hong Kong. The research focuses on mainland students’ adaptation experiences upon arrival in Hong Kong, including their strategies and motivations. To these ends, the linguistic and socio-cultural adaptation experiences these mainland Chinese students encountered in their first year of university study were investigated and study through a mixed-method approach. The theoretical framework, push-pull model, has enabled the exploration in different levels, including macro and micro. Findings concluded that the confusion of “bilingualism” and language barrier, especially Cantonese, were linguistic adaptation experiences participants faced. In the socio-cultural aspect, findings showed that friendship, discrimination, culture, identity, loneliness and politics were experiences faced. Findings also showed that participants dealt with and managed these experiences through different coping strategies including taking Cantonese lessons, making friends only with students of similar background, soliciting help from local friends, joining local student societies, endurance and acceptance, “let nature takes it course”, and have not found ways to cope. The study also revealed that assistance provided by university is insufficient and needs improvement. The implications of this study impact research on student support and identity formation.